Spatial sputtering of fused silica after a laser-induced exploding caused by a 355 nm nd: YAG laser - Peng, Ge; Zhang, Peng; Dong, Zhe; Chen, Jiaxuan; Liang, Lingxi; Zhu, Chengyu; Gao, Qiang; Lu, Lihua (Frontiers in Physics, 2022)
To alleviate laser-induced threats in the high-power laser systems, it is necessary to under-stand the debris propagation process and distribution characteristics, then take protection and cleaning strategies to sustain an ultra-clean environment. This work presents an experimental investigation of the sputtering behaviors of the laser-induced fused silica debris to clarify their longitudinal propagation and bottom distribution on the millimeter scale. Two types of pol-ished surfaces with more than three orders of magnitude differences in surface roughness were adopted. The result reveals the centralized/decentralized distribution and the ability of long-range movement of debris propelled by the melting and mechanical failure. The maxi-mum largest dispersion angle (LDA) appears at 18J/cm2 for debris within 10-20 μm from the Two Sides polished surface; debris <30 μm dominate the major quantity in the longitudinal propagation, and their centralization ability profoundly relies on the laser fluence and the surface roughness of the target; the diameter of the debris with long-range movement gener-ally below 20 μm. This study could guide for establishing the overall dynamic cleaning strat-egy inside the high-power laser systems.